What Drives Female Labor Force Participation? Comparable Micro-Level Evidence from Eight Developing and Emerging Economies - Stephan Klasen; Janneke Pieters; Manuel Santos Silva; Le Thi Ngoc Tu (Institute of Labor Economics (IZA), 2019)
We investigate the micro-level determinants of labor force participation of urban married women in eight low- and middle-income economies: Bolivia, Brazil, India, Indonesia, Jordan, South Africa, Tanzania, and Vietnam. In order to understand what drives changes and differences in participation rates since the early 2000s, we build a unified empirical framework that allows for comparative analyses across time and space. We find that the coefficients of women's characteristics differ substantially across countries, and this explains most of the between-country differences in participation rates. In particular, the relationship between a woman's education and her participation in the labor force varies from being positive and linear (Brazil and South Africa) to being U- or J-shaped (India, Jordan, and Indonesia), or a mixture of both (Bolivia, Vietnam, and Tanzania). Overall, the economic, social, and institutional constraints that shape women's labor force participation remain largely country-specific. Nonetheless, rising education levels and declining fertility consistently increased participation rates, while rising household incomes contributed negatively in relatively poorer countries, suggesting that a substantial share of women work out of economic necessity.
Keywords: J20; J16; I25; O15; 330; female labor force participation; gender; labor markets; development